Problems of Implementing Legal Measures on Attracting Investment and Supply Chain Strategy to the Economy of the Republic of Kazakhstan - M.A. Sarsembaev; D.M. Sarsembaev; A.K. Kussainova; L.T. Nazarkulova (International Journal of Supply Chain Management, 2020)
Abstract— The manuscript considers the main international legal and national legal measures to attract investment and supply chain strategy in the economy of the Republic of Kazakhstan on the example of one of the priority sectors of the economy - transport and logistics and also suggests ways to solve them. The authors identified several problems in this area: a combination of private and general social interests, attracting private investment in the translogistical industry, ensuring a balance of national and foreign investments, guaranteeing the rights of investors, and legal regulation of investment policies. The authors substantiate that for more systematic measures to attract investment and apply the supply chain strategy in the country's economy, it would be advisable to develop a state investment policy for the long term, considering measures to attract private direct investment in priority sectors of Kazakhstan's economy, but not attractive for private investors, as well as providing for measures for international cooperation in this area. The tendency of supply chain development programs to be captured by small-business lobbies, and the willingness of international donors to tolerate, even promote this, has adverse consequences for emerging economies.